THE DESIGN AND TECHNOLOGY IMPROVING OF THE FREIGHT CARS REPAIR - Myamlin, S. V.; Panasenko, V. Ya.; Klymenko, I. V. (Science and Transport Progress, 2007)
In this paper some solutions to improve cargo cars construction were proposed these solutions help also to improve the conditions of work at railway field and safety of trains movements.